Developing twenty-first-century skills in out-of-school education: the Bridge21 Transition Year programme. Issue 4 (8th August 2021) - Sullivan, Kevin; Bray, Aibhín; Tangney, Brendan
ABSTRACT: Twenty-first-century (21 C) skills need to be taught intentionally and well, using pedagogical approaches that engage students and help them learn both skills and curriculum content. This article describes an instrumental case study of an out-of-school education programme (Bridge21) designed to help students develop 21 C skills. In order to determine the effectiveness of the programme, a mixed-methods approach was employed that included the collection of quantitative and qualitative data using student surveys ( N = 329) and group interviews. A detailed skills framework was used to analyse which skills are inherent to the various activities that make up the programme. Findings suggest that the Bridge21 model can provide significant and sustained increases in student confidence across a range of skills, and that various elements of the programme design contribute directly to this.